Wh-question in Malay: an explanation for the restriction of extraction to subject position with yang - Wong, Bee Eng (Penerbit Universiti Kebangsaan Malaysia, 2008)
In wh-question formation in standard Malay, only extraction from the subject position is possible. This is in contrast to the English language, where extraction is possible from positions lower than the subject position. In fact, in Malay, any argument in a position lower than that of a subject has to be passivised to become a derived subject before extraction can occur. When an extraction occurs, from an embedded clause in question formation, the verb in the matrix clause has to be passivised as well. In this paper, an explanation is offered to account for this phenomenon in standard Malay. The framework adopted to explain the phenomenon is based on the principles and parameters approach (see Chomsky, 1981a, 1981b, 1986a, 1991), and the Minimalist Programme (See Chomsky, 1995). In particular, Rizzi’s theory of relativised minimality and its conjunctive notion of the Empty Category Principle (ECP) (1990) are referred to. Additionally, Shlonsky’s treatment of Palestinian Arabic relativisation (1992) is extended to Malay wh-question formation. The motivation for such an exercise is that this will have implications in terms of contribution to the body of literature in Malay linguistics, particularly from the generative perspective.